2020
DOI: 10.2176/nmc.ra.2020-0111
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique for Carotid Endarterectomy: Current Methods and Problems

Abstract: Over the last 60 years, many reports have investigated carotid endarterectomy (CEA) and techniques have thus changed and improved. In this paper, we review the recent literature regarding operational maneuvers for CEA and discuss future problems for CEA. Longitudinal skin incision is common, but the transverse incision has been reported to offer minimal invasiveness and better cosmetic effects for CEA. Most surgeons currently use microscopy for dissection of the artery and plaque. Although no monitoring techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 94 publications
0
29
0
1
Order By: Relevance
“…After establishment of the airway (AW), the patient is placed in a supine position, arms along the body, and with hyperextension and contralateral rotation of the neck, facilitating more distal dissection of the ICA. 21 , 34 , 63 However, excessive movements can cause compression of the vertebral arteries or the contralateral carotid, 64 in addition to making SCM muscle retraction difficult because of increased muscle tension and restricting the mobility of the CCA and the carotid bifurcation. 65…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After establishment of the airway (AW), the patient is placed in a supine position, arms along the body, and with hyperextension and contralateral rotation of the neck, facilitating more distal dissection of the ICA. 21 , 34 , 63 However, excessive movements can cause compression of the vertebral arteries or the contralateral carotid, 64 in addition to making SCM muscle retraction difficult because of increased muscle tension and restricting the mobility of the CCA and the carotid bifurcation. 65…”
Section: Discussionmentioning
confidence: 99%
“…Após o estabelecimento da via aérea (VA), o paciente é colocado em posição supina, com os braços ao longo do corpo, hiperextensão e rotação contralateral do pescoço, facilitando a dissecção mais distal da ACI 21 , 34 , 63 . Entretanto, movimentos excessivos podem resultar em compressão das artérias vertebrais ou da carótida contralateral 64 , além de dificultar a retração do ECM por aumentar a tensão do músculo e restringir a mobilidade da ACC e da bifurcação carotídea 65 .…”
Section: Discussionunclassified
“…A subgroup analysis of the CREST (Carotid Revascularization Endarterectomy Versus Stenting Trial) study showed that the use of a patch in CEA could significantly reduce the occurrence of restenosis after 2 years compared with DC (3.1% vs. 10.7%, hazard ratio =0.35) (5). At present, the use of patches may present some challenges, such as prolonged operation time, graft-related infection, thrombosis, aneurysmal dilatation, and other issues (11,25). However, few studies have compared the intimal growth between PC and DC after CEA.…”
Section: Discussionmentioning
confidence: 99%
“…After establishment of the airway (AW), the patient is placed in a supine position, arms along the body, and with hyperextension and contralateral rotation of the neck, facilitating more distal dissection of the ICA. 21,34,63 However, excessive movements can cause compression of the vertebral arteries or the contralateral carotid, 64 in addition to making SCM muscle retraction difficult because of increased muscle tension and restricting the mobility of the CCA and the carotid bifurcation. 65 Surgical AW and nasotracheal intubation (NTI) increase the number of possible techniques for exposure of the DCSICA or an HCB, making temporary mandibular subluxation (TMS) a viable option.…”
Section: Considerations Relating To Airways and Patient Positioningmentioning
confidence: 99%